Universal salt-assisted assembly of MXene from suspension on polymer substrates - Liang Zhao; Lingyi Bi; Jiayue Hu; Guanhui Gao; Danzhen Zhang; Yun Li; Aidan Flynn; Teng Zhang; Ruocun Wang; Xuemei M. Cheng; Ling Liu; Yury Gogotsi; et al. (Nature Communications)
Abstract Two-dimensional carbides and nitrides, known as MXenes, are promising for water-processable coatings due to their excellent electrical, thermal, and optical properties. However, depositing hydrophilic MXene nanosheets onto inert or hydrophobic polymer surfaces requires plasma treatment or chemical modification. This study demonstrates a universal salt-assisted assembly method that produces ultra-thin, uniform MXene coatings with exceptional mechanical stability and washability on various polymers, including high-performance polymers for extreme temperatures. The salt in the Ti3C2T x colloidal suspension reduces surface charges, enabling electrostatically hydrophobized MXene deposition on polymers. A library of salts was used to optimize assembly kinetics and coating morphology. A 170 nm MXene coating can reduce radiation temperature by ~200 °C on a 300 °C PEEK substrate, while the coating on Kevlar fabric provides comfort in extreme conditions, including outer space and polar regions.